PRN usage before and after discharge from a forensic inpatient unit: A series example of patients with intellectual disabilities. Issue 2 (23rd November 2022) - Busch, Louis; Saini, Valdeep; Budin, Radek; Jones, Roland M.
Abstract: Adults living with intellectual and developmental disabilities are often prescribed psychotropic medication on an "as needed" basis (PRN) in response to behavioural challenges. In the present study we conducted a retrospective analysis of medication administration records in the 6‐months preceding and following discharge of 11 adults with intellectual and developmental disabilities to community settings from forensic inpatient units within a mental health hospital. We found a significant reduction in the frequency of PRN usage after discharge. We propose potential reasons for the difference in PRN administration across settings and make suggestions for future research.